Analysis of Land Dispute Resolution Due to Dual Certificates in Indonesia (Study of Supreme Court Decision Number 217/PDT/2021/PT KPG) - Muhamad Aria Torik Akbar; Kaharuddin Kaharuddin (Law Development Journal, 2025)
This study discusses the resolution of land disputes resulting from duplicate certificates using a case study of Supreme Court Decision Number 217/PDT/2021/PT KPG. The main issues examined include the causes of the duplicate certificates, the validity of each certificate according to the Basic Agrarian Law (UUPA), and their implications for legal protection for legitimate certificate owners. The research method used is normative juridical with a statutory and case-based approach. The results show that the duplicate certificates arose due to administrative and measurement errors by the Ende Regency Land Agency (BPN), which resulted in an overlap between Land Ownership Certificate Number 153 in the name of Asnah Achmad and Number 658 in the name of Muhamad Adolf Sir. The Supreme Court ruled that the certificate issued earlier has valid legal force. This decision strengthens the principles of legal certainty, justice, and the state's responsibility in providing legal protection for legitimate land owners, and serves as a basis for improving the land administration system in Indonesia.